Kolaborasi Pemerintah Daerah Riau Dalam Implementasi Rencana Aksi Nasional P4GN - Dewi Oktafia Eka Putri; Indra Mardeni; Ichsan Malik; I. Gede Sumertha; Pujo Widodo; Herlina J Saragih (Faculty of Social Science, Universitas Negeri Padang, 2023)
Indonesia is currently facing quite serious challenges in terms of the abuse of narcotics and illegal drugs. In general, narcotics and psychotropic substances can be used as medicinal ingredients in the medical field and in the development of science. The effects of this dependence can result in death. Not only that, other aspects such as moral and social are also affected by narcotics abuse. One of the biggest problems in Riau is the high circulation of drugs coming from abroad. The high distribution of drugs is influenced by various factors, in this case, geographical and demographic conditions in Riau. Based on the identification of drug-handling problems in Riau Province that have been explained, this paper has the objectives of, among others, analyzing efforts to implement P4GN, especially in the context of tackling drug trafficking and abuse in Riau Province; and analyze efforts to implement P4GN in Riau from a national security perspective. This research approach is qualitative with a descriptive research design. The research location is in Riau Province with the determination of informants using a purposive sampling technique. Collaborative governance focuses on the voluntary aspects of collaborative practice. From the voluntary aspect is expected that every actor involved can work optimally to achieve goals in the effort to implement P4GN in Riau Province. Communities, especially in Riau and throughout Indonesia in general, to correctly understand the concept of national security in a comprehensive manner.